От составителей [Gabriel Superfin at 80: Section Editors’ Note] - Okhotin, Nikita; Ospovat, Alexander; Timenchik, Roman (Slavica Revalensia, 2023)
This brief note preceds the section, which contains 10 articles written on the occasion of the 80th birthday of Gabriel Superfin—a scholar, a human rights activist, and one of the brightest minds of his generation. The section’s contributors are Alexander Ospovat (Moscow / Los Angeles), Alexander Sobolev (Moscow / Jerusalem), Roman Timenchik (Jerusalem), Alexander Lavrov (St. Petersburg), Alexander Dolinin (Madison / St. Petersburg), Irina Belobrovtseva (Tallinn), Fedor Poljakov (Vienna), Georgii Levinton (St. Petersburg), Galina Lapina (Madison / St. Petersburg), and Boris Ravdin (Riga).